Use of English Movies as a Pedagogical Tool in Learning English Language - Walay, Analyn (International Journal of Arts, Sciences and Education, 2022)
In a world of language globalization, the English language plays a crucial role as people tend to learn and master the language to cope with this dynamic transition. Therefore, teachers have been presenting English movies as these movies provide an authentic English environment. Thus, this study aimed to explore the use of English movies as a pedagogical tool in learning the English language among grade VII students. Specifically, it determined the extent of preference for the English movie genre and the extent of effectiveness of English movies as a tool for learning the English language as perceived by the students. A descriptive research design was employed in the study. The study revealed that the grade VII students often preferred the English movie genre as a tool in learning the English language. Students learned the English language best when they are watching comedy being described as often preferred. Furthermore, they perceived and considered the integration of English movies as much effective tool for learning the English language, especially its benefits on improving their pronunciation which was manifested and described as very much effective.